Chrysotus Meigen (Diptera: Dolichopodidae) from China with descriptions of five new species belonging to the Ch. laesus-group. (3rd July 2017) - Zhou, Zhengxiang; Wei, Lianmeng
Abstract: Five new species belonging to the Chrysotus laesus -group redefined by Wei and Zhang are described and illustrated, and the group is divided into 5 species-subgroups: adunatus -subgroup, brevicercus -subgroup, nudisetus -subgroup, laesus -subgroup, trapezinus -subgroup. A key to the Chrysotus species groups known from China and all 22 species assigned to Ch. laesus species-group are provided. The type specimens of the new species are deposited in the Anshun Centre for Disease Prevention and Control, Anshun, Guizhou (ACDPCAG). http://www.zoobank.org/urn:lsid:zoobank.org:pub:0151F59F-A22C-4900-92B3-82F1AE0A698F